ALCOHOL- AND DRUG-RELATED CONTENTS IN THE NURSING PROGRAM AT ESPÍRITO SANTO FEDERAL UNIVERSITY: A CRITICAL ANALYSIS - Marluce S. Macieira; Marcio W. Camata; Elisangela C. Santos; Sandra C Pillon; Robison Boni (Revista Eletrônica de Enfermagem, 2004)
The study was based on the project sponsored by the Organization of American States which wasdeveloped by São Paulo Federal University College of Nursing aiming at analyzing the alcohol- and drug-relatedcourse contents taught in undergraduate nursing programs in Brazil. Its purpose was to evaluate teachingconditions concerning this theme in the undergraduate nursing program at Espírito Santo Federal Universitythrough a descriptive survey applied to 86 nursing students. To 95% of the students, the problem related to theconsumption of alcohol and drugs is a theme of great interest. The inclusion of these themes in nursing programsis a facilitating condition for the education of nurses in this area.